Effects of NaNO3 and KNO3 in Kosaric fertilizer on the growth of Arthrospira platensis - Muhamad Nor, Norsalwani; Bajis, Halisa; Omar, Hishamuddin; Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
This study was carried out to determine whether the replacement of NaNO3 to KNO3 in Kosaric media can give better growth to Arthrospira platensis. The growth of A. platensis in different culture media was which are Kosaric media and Kosaric media with the modifications of NaN03 to KNO3 at concentration of 0.75, 1.25, and 1.75g/L in indoor condition. The pH value for Kosaric media shows the highest reading which is 9.63, followed by both modified Kosaric media with the addition of 1.25g/L KNO3 and 1.75g/L KNO3 which have the same reading of 9.58, and 9.56 for modified Kosaric media with the addition of 0.75g/L KNO3. Cell dry weight is 2.13mg/L for modified Kosaric media, I.78mg/L for modified Kosaric media with the addition of l .25g/L KNO3, 1.61 mg/L. for modified Kosaric media with the addition of 0.75g/L KNO3 and 1.18mg/L for Kosaric media. While for chlorophyll a content, Kosaric media shows the highest value which is 2.79mg/L, followed by modified Kosaric media with the addition of 1.75b/L KNO3 (1.65mg/L), modified Kosaric media with the addition of 1.25g/L KNO3 (1.29mg/L), and modified Kosaric media with the addition of 0.75g/L KNO3 (1.09mg/L). Kosaric media is still the best culture media for culturing of A. platensis. Except for cell dry weight, the modified Kosaric media with the addition of 1.75g/L KNO3 shows the highest reading. The alternative commercial fertilizer that are cheaper than Kosaric media are hoped to replace Kosaric media in culturing A. platensis.